KONFORMITAS KELOMPOK, HARGA DIRI DAN EFIKASI DIRI SEBAGAI PREDIKTOR PERILAKU KETIDAKJUJURAN AKADEMIK PADA SISWA - Setya Putri Lestari; Sri Lestari (Jurnal Penelitian Humaniora, 2017)
This research is aimed to analyze group conformity, self-esteem and self-efficacyempirically as predictors of academic dishonesty behavior on MTsN students.Hypothesis is conducted by applying regression analysis.Data collecting used on thisresearch are four scale measurements of academic dishonesty, group conformity, selfesteemand self-efficacy. Respondents involved in this research are 280 students ofMTsn between 12 to 16 years old range, consisting 138 male students and 142 femalestudents. The analysis shows that group conformity, self-esteem and self-efficacyvariables contribute 39,7 % toward students’ academic dishonesty. Conclusively, theresult of this research confirms that group conformity, self-esteem and self-efficacyare predictors of academic dishonesty on MTsN students. The strongest variableamong them is group conformity.